Low-frequency noise pollution impairs burrowing activities of marine benthic invertebrates. (1st October 2022) - Wang, Sheng V.; Wrede, Alexa; Tremblay, Nelly; Beermann, Jan
Abstract: Sounds from human activities such as shipping and seismic surveys have been progressively invading natural soundscapes and pervading oceanic ambient sounds for decades. Benthic invertebrates are important ecosystem engineers that continually rework the sediment they live in. Here, we tested how low-frequency noise (LFN), a significant component of noise pollution, affects the sediment reworking activities of selected macrobenthic invertebrates. In a controlled laboratory setup, the effects of acute LFN exposure on the behavior of three abundant bioturbators on the North Atlantic coasts were explored for the first time by tracking their sediment reworking and bioirrigation activities in noisy and control environments via luminophore and sodium bromide (NaBr) tracers, respectively. The amphipod crustacean Corophium volutator was negatively affected by LFN, exhibiting lower bioturbation rates and shallower luminophore burial depths compared to controls. The effect of LFN on the polychaete Arenicola marina and the bivalve Limecola balthica remained inconclusive, although A. marina displayed greater variability in bioirrigation rates when exposed to LFN. Furthermore, a potential stress response was observed in L. balthica that could reduce bioturbation potential. Benthic macroinvertebrates may be in jeopardy along with the crucial ecosystem-maintaining services they provide. More research is urgently needed to understand, predict, and manage the impacts of anthropogenic noise pollution on marine fauna and their associated ecosystems. Graphical abstract: Image 1 Highlights: Low-frequency noise (LFN) affects burial behavior of marine amphipods. Polychaetes and bivalves seemed unaffected statistically by LFN, however … Bivalves exhibited potential anti-burrowing stress response when exposed to LFN. Polychaetes exhibited larger variation in burial and ventilation behaviors.